Motor unit tracking using blind source separation filters and waveform cross-correlations: reliability under physiological and pharmacological conditions - Goodlich, Benjamin I.; Del Vecchio, Alessandro; Kavanagh, Justin J. (Journal of Applied Physiology, 2023)
Recent advancements in the analysis of high-density surface electromyography (HDsEMG) have enabled the identification, and tracking, of motor units (MUs) to study muscle activation. This study aimed to evaluate the reliability of MU tracking using two common methods: blind source separation filters and two-dimensional waveform cross-correlation. An experiment design was developed to assess physiological reliability and reliability for a drug intervention known to reduce the discharge rate of motoneurones (cyproheptadine). HDsEMG signals were recorded from tibialis anterior during isometric dorsiflexions to 10, 30, 50, and 70% of maximal voluntary contraction (MVC). MUs were matched within session (2.5 h) using the filter method, and between sessions (7 days) via the waveform method. Both tracking methods demonstrated similar reliability during physiological conditions [e.g., MU discharge: filter intraclass correlation coefficient (ICC): 10% of MVC = 0.76, to 70% of MVC = 0.86; waveform ICC: 10% of MVC = 0.78, to 70% of MVC = 0.91]. Although reliability slightly reduced after the pharmacological intervention, there were no discernible differences in tracking performance (e.g., MU discharge filter ICC: 10% of MVC = 0.73, to 70% of MVC = 0.75; waveform ICC: 10% of MVC = 0.84, to 70% of MVC = 0.85). The poorest reliability typically occurred at higher contraction intensities, which aligned with the greatest variability in MU characteristics. This study confirms that the tracking method may not impact the interpretation of MU data, provided that an appropriate experiment design is used. However, caution should be used when tracking MUs during higher-intensity isometric contractions.NEW & NOTEWORTHY The most direct way to validate longitudinal tracking of motor unit data extracted from high-density surface electromyography is to contrast findings with intramuscular electromyography. We used pharmacology to induce changes in motor unit discharge properties as a noninvasive alternative to validate the reliability of tracking motor units. This study confirmed that the specific tracking method may not impact interpretation of motor unit data at lower contraction intensities; however, caution should be used when tracking units during higher intensities.
CRIS-Team Scopus Importer:2023-08-11
Keywords: decomposition; high-density surface EMG; motoneurones; motor unit matching; tibialis anterior